Irrigation with desalinated water: A step toward increasing water saving and crop yields. Issue 1 (21st January 2015) - Silber, Avner; Israeli, Yair; Elingold, Idan; Levi, Menashe; Levkovitch, Irit; Russo, David; Assouline, Shmuel
Abstract: We examined the impact of two different approaches to managing irrigation water salinity: salt leaching from the field ("conventional" management) and water desalination before field application ("alternative" management). Freshwater commonly used for irrigation (FW) and desalinated water (DS) were applied to the high‐water‐demanding crop banana at four different rates. Both irrigation rate and water salinity significantly affected yield. DS application consistently produced higher yields than FW, independently of irrigation rate. The highest yield for FW‐irrigation was achieved with the highest irrigation rate, whereas the same yield was obtained in the case of DS‐irrigation with practically half the amount of water. Yield decreased with FW‐irrigation, even when the water salinity, ECi, was lower than the limit considered safe for soil and crops. Irrigating with FW provided a massive amount of salt which accumulated in the rhizosphere, inducing increased osmotic potential of the soil solution and impairing plant water uptake. Furthermore, applying the "conventional" management, a significant amount of salt is leached from the rhizosphere, accumulating in deeper soil layers, and eventually reaching groundwater reservoirs, thus contributing to the deterioration of both soil and water quality. Removal of salt excess from the water before it reaches the field by means of DS‐irrigation may save significant amounts of irrigation water by reducing the salt leaching requirements while increasing yield and improving fruit quality, and decreasing salt load in the groundwater. Key Points: Conventional irrigation management adds a massive load of salt Desalination save significant amounts of water while increasing yield Desalination improves crop quality and reduces salt load in the groundwater